Comparative Study of Hemoglobin Levels: Adolescents in The Highlands and Lowlands of Blitar Regency, East Java - Prodyanatasari, Arshy; Purnadianti, Mely; Putri, Mardiana Prasetyani (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. Indonesia's geographical area appears to be separated into two regions: highlands and lowlands. Highlands impact hemoglobin levels. Because of the decreased partial pressure of oxygen and the body's acclimatization response, being at a high altitude results in hypoxia. In order to adjust to low oxygen levels, hemoglobin levels rise. This study aimed to compare hemoglobin levels using the hemoglobin POCT test among teenagers residing in the lowlands of Blitar Regency, East Java. Methods. Purposive sampling is used in the research method, which employs a cross-sectional approach. The sample is chosen using inclusion and exclusion criteria. Results. With an average hemoglobin level of 14.6833 g/dl, teenagers in the Highlands had normal hemoglobin levels for up to five of them (42%), and abnormal hemoglobin levels for seven of them (58%). The average hemoglobin level among teens in the lowlands was 12.2333 g/dl, with three (25%) and nine (75%) having normal levels. Using the Independent T-Test, the data analysis revealed a significant value of 0.038 <0.05. Conclusion. Hemoglobin levels of adolescents who live in the highlands of Semen Village RT. 03 RW. 04 had an average hemoglobin level of 14.6833 g/dl, and hemoglobin levels in adolescents who lived in the lowlands of Sutojayan Village, RT. 01 PC. 04 with an average hemoglobin level of 12.23 g/dL and a significance value of 0.038.